Film Dokumenter Silek Tuo Gunuang - Rinaldy Hadie Apriyus; Eliya Pebriyeni (Departement of Mathematics Education, 2023)
Modernization and changes in lifestyles that have begun to be acculturated with foreign cultures have made this culture fade little by little. Answering the challenges of the times requires an audio-visual media in the form of documentary films as a documentation archive so that it can be passed on by the next generation and reintroduced silek tuo gunuang effectively and efficiently. The design aims to digitally archive silek tuo gunuang as a cultural heritage that must be preserved through documentaries to the public, especially the people of the city of Padang Panjang. Using the 4D planning method (Four –D). Consists of (Define), (Design), (Develop) and (Desseminate). SWOT analysis approach. The main media is in the form of this documentary film, providing historical information, permitting flow, requirements and other information from this silek, and due diligence has been carried out on several people, ranging from academics, practitioners and the public in general, received a positive response, it can be concluded that the film is suitable for distributed, with supporting media in the form of movie trailers, posters, x-banners, stickers and t-shirts to support the delivery of information from this documentary.